2018
DOI: 10.29333/ajqr/5797
|View full text |Cite
|
Sign up to set email alerts
|

Academic success and resiliency factors: A case study of unaccompanied immigrant children

Abstract: The purpose of this study was to identify resiliency factors that led to the academic success of three unaccompanied immigrant students in a Texas high school. We used case study methodology to examine the real life context of a phenomenon with data collected from three student participants in their natural settings using interviews, participant observations at school, and photo-elicitation. The findings indicated that internal and external protective factors attributed to the resiliency and school success of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…According to Baxter and Jack (2010), open-ended interviews in carrying out case study especially focusing on small sample is one of the efficient way to collect in-depth exploration as compared to surveys. This can be seen in the excellent works of some other qualitative researchers (Kratt, 2018;Peña, Jones, Orange, Simieou, & Márquez, 2018).…”
Section: Data Collectionmentioning
confidence: 79%
“…According to Baxter and Jack (2010), open-ended interviews in carrying out case study especially focusing on small sample is one of the efficient way to collect in-depth exploration as compared to surveys. This can be seen in the excellent works of some other qualitative researchers (Kratt, 2018;Peña, Jones, Orange, Simieou, & Márquez, 2018).…”
Section: Data Collectionmentioning
confidence: 79%
“…Resilience is a significant academic achievement determinant (Leary & DeRosier, 2012); it enables students show persistence and get over academic difficulties like an exam failure. Previous studies have revealed that resilient students are often distinct concerning a collection of school behaviors specifically and explicitly linked to learning (Finn & Rock, 1997; Peña et al, 2018). These behaviors, such as getting to class and school on time, being ready to and take part in the class assignments, expending the effort needed to complete tasks in school, and as homework, behaving compatibly in class revealed huge and important distinctions between resilient and non‐resilient learners.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers postulate three main components of ethnic identity: affection, cognition, and behaviors (Kwan & Sodowsky, 1997;Peña et al, 2018;Phinney et al, 1992;Uba, 1994). Individuals' affection refers to their feelings of engaging with and belonging to their ethnic group.…”
Section: Components Of Ethnic Identitymentioning
confidence: 99%